Student Absenteeism in Mathematics Lessons: Social Variables in the PGS of Namibe - Eduardo Chaves-Barboza; José-Antonio; Ana-Paula Sa; Juan-Manuel Tr (MDPI AG, 2019)
This article analyses social variables that cause student absenteeism from mathematics classes. It contrasts teachers’ perceptions with the perceptions of students undertaking their second and third levels of a Bachelor’s degree in Physics and Chemistry at the Pedagogical Graduate School (PGS) of Namibe, Angola. To perform this analysis, a Likert scale questionnaire was undertaken and descriptive and inferential statistical tests, a correlation analysis, a variance analysis, and a multivariate factorial analysis were carried out on the data. The results showed that lack of financial and emotional support from students’ families and the students’ discomfort upon moving to the educational centre were reasons behind absenteeism in mathematics lessons.